Case Report: Markedly Long-Term Preservation of Pancreatic β‐Cell Function in a Subject With Elderly Onset of Type 1 Diabetes Mellitus Showing High-Titer Autoimmune Antibodies for Over 4 Years - Shigemoto, Ryo; Anno, Takatoshi; Kawasaki, Fumiko; Kaku, Kohei; Kaneto, Hideaki (Frontiers in immunology, 2021)
Type 1 diabetes mellitus (T1DM) is mainly triggered by autoimmune β-cell destruction, usually leading to absolute insulin deficiency. Regarding the speed of β-cell destruction, there are large variations depending on age. In some adult cases, sufficient β-cell function is sometimes retained for a relatively long period and eventually they become dependent on insulin for survival. It is known that even in subjects with T1DM showing high titers of such antibodies, insulin secretory capacity is preserved under several conditions such as “honeymoon” period and slowly progressive T1DM (SPIDDM). Herein, we reported the acute onset T1DM subject with long-term preservation of β-cell function, although his anti-GAD antibody and anti-IA-2 antibody titers were very high for more than 4 years. This case is very important in that his β-cell function was preserved with dipeptidyl peptidase-4 inhibitor alone. This means that there are large variations in the speed of β-cell destruction in the onset of T1DM.